(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The intended research work viz. A critical study on Book-Keeping and accounting practices followed by the small tea growers is designed to find out how the small tea growers of Assam and specifically the small tea growers of Charaideo District keep the records of their business in terms of financial transactions made in the process of carrying out the business successfully. The researcher lays emphasis on the knowledge of Book-Keeping and accounting practices to be acquired by the small tea growers to ascertain the profit or loss of their business concerned. To make the study systematic and scientific, the researcher uses survey method for gathering information from the small tea growers directly through direct visits, observations, interviews and administration of questionnaires. Problems encountered by the small tea growers in maintaining proper accounts of their business are highlighted through the study. Both qualitative and quantitative analysis have been made to assure the authenticity of the research work. The book-keeping and accounting processes followed by the small tea growers of the surveyed area have been clearly highlighted through this study and the advantages and disadvantages of the practices adopted by the small tea growers have also been focused for information of the future entrepreneurs in the field of tea growing enterprise.